Finland : Selected Issues and Analytical Notes. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues and Analytical Note on Finland discusses the potential spillovers to Finland from various shocks associated with cross-country interlinkages. The note provides an overview of the trade and financial linkages, assesses the impact of global fiscal consolidation on Finland via trade links, quantifies dynamic contributions from external sources to growth, and uses these contributions to forecast the potential loss to Finnish GDP from a growth slowdown in other European countries; and analyzes the potential impact from the banking sector or sovereign stress.